The other journeys (Journal of Parents and Teachers, 2014)
Nowadays we are in a globalised society, so tourism and travel is considered a leisure activity. However, this article goes back to one of the journeys that marked the passage from one historical stage to another. It refers to one of the greatest migratory movements in history, the journey from Europe to the New Worlds. With regard to current migratory movements, words such as pateras, surge, etc. appear in the media. However, the vast majority of immigrants are part of the group of tourists who travel by land or air.
Keywords: migrations; Europe; travel; journey; history; New World